15 Implementation of a novel telephone clinic service to the ni inherited cardiac conditions service. (31st October 2017) - Thompson, Patrick; McOsker, Joanne; Jardine, Tracy; McCall, Damian; McKeown, Pascal; Muir, Alison
Abstract : Context: Inherited Cardiac Conditions (ICCs) are genetic diseases affecting the heart, associated with an increased risk of sudden cardiac death. The Northern Ireland regional ICC service, where patients with ICCs and their first degree relatives are assessed and offered genetic testing to identify the causative DNA mutation undertook this service development to reduce the time from genetic testing to result discussion. Assessment of problem and analysis of its causes Auditing of genetic testing between August and October 2015 identified a delay of 86 days from laboratory report to discussion with the patient due to a lack of outpatient clinic capacity. The ICC multidisciplinary team designed an altered approach to genetic counselling and delivery of results to make optimal use of already available resources and introduced a novel telephone clinic. The pilot telephone clinic launched in April 2016 with subsequent increasing capacity and then a repeat audit during the same time period in 2016 after implementation of the telephone clinic service was undertaken. The average time delay from genetic results to patient discussion was reduced from 85.7 to 43.8 days. A qualitative assessment by patient satisfaction survey (response rate 20/47 (43%)) was extremely positive. 100% of responders felt happy to receive their results by telephone 100% indicated they would wish to receive results by telephone in the future. Effects of Changes: Implementation of a telephone clinic has achieved the goal of significantly reduced waiting times (49% shorter) with excellent service quality, demonstrating that meaningful improvements can be made with minimal changes to practice and without significant additional resources. Future development of this service includes plans to increase capacity further and transform it into a nurse-led service.